The Effect of Cause Related Marketing on Arua Phinisi Consumer Purchase Interest with Brand Image as Moderating Variable - Diah Ari Tapaningtyas (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study aims to determine the influence of cause related marketing on Arua Phinisi’s consumer purchase intention with brand image as a moderating variable. The number of respondents involved in this study are 55 respondents. All respondents are Arua Phinisi customers in 2020. Data in the study were obtained from the results of distributing questionnaires, which then analyzed using the Partial Least Square technique with the help of SmartPLS software. Based on the results of the analysis in this study, the following results were obtained: (1) cause related marketing has a positive and significant influence on purchase intention, the better the cause related marketing carried out by Arua Phinisi, the higher the consumer purchase intention; (4) brand image can moderate the influence of cause related marketing on Arua Phinisi’s consumer purchase intention, a strong brand image will strengthen the influence of cause related marketing on consumer purchase intention.